Web Content Management Systems: An Analysis of Forensic Investigatory Challenges. Issue 5 (26th February 2018) - Horsman, Graeme
Abstract: With an increase in the creation and maintenance of personal websites, web content management systems are now frequently utilized. Such systems offer a low cost and simple solution for those seeking to develop an online presence, and subsequently, a platform from which reported defamatory content, abuse, and copyright infringement has been witnessed. This article provides an introductory forensic analysis of the three current most popular web content management systems available, WordPress, Drupal, and Joomla! Test platforms have been created, and their site structures have been examined to provide guidance for forensic practitioners facing investigations of this type. Result's document available metadata for establishing site ownership, user interactions, and stored content following analysis of artifacts including Wordpress's wp_users, and wp_comments tables, Drupal's "watchdog" records, and Joomla!'s _users, and _content tables. Finally, investigatory limitations documenting the difficulties of investigating WCMS usage are noted, and analysis recommendations are offered.